Comparison between Coblation and Bipolar Diathermy Tonsillectomy in Children at a Tertiary Level Hospital of Nepal - Bajracharya, Rohita; Bhandari, Ramesh; Neupane, Yogesh; Guragain, Rajendra Prasad Sharma (Journal of Bharatpur Hospital, 2025)
Background The ideal method of tonsillectomy should decrease operative time, blood loss, postoperative pain and postoperative hemorrhage. This study was done to compare operative time and early postoperative pain between coblation and bipolar diathermy tonsillectomy in children. Methods A Prospective comparative study was conducted from May 2019 to April 2020 in children up to age 14 years who underwent tonsillectomy either by coblation or bipolar diathermy. For operative time, three parameters were recorded: total time from mouth gag insertion to gag removal, time from incision to hemostasis for right tonsil and time from incision to hemostasis for left tonsil. Post tonsillectomy pain was assessed using FLACC score for children up to five years and Numeric rating scale- Faces rating scale (NRS-FRS) for children older than five years. Analgesics use on fourth and fifth postoperative day were also recorded. Results Forty-nine children were enrolled in the study. Total of 25 patients in coblation and 24 patients in bipolar diathermy group. The mean operative time measured was 33.14 min for coblation and 25.04 min for bipolar group. The difference was statistically significant (p-value=0.005). Postoperative pain on third, fourth and fifth days were significantly less in coblation group. However, there was no statistically significant difference in intake of analgesics between the two groups. Conclusions Tonsillectomy in children using coblation technique was found to take longer operative time compared to bipolar diathermy tonsillectomy. However, early postoperative pain was significantly lower in coblation group.